Das Hatschepsut-Puzzle : die Pharaonin und ihr rätselhafter Flakon - hautnah - Höveler-Müller, Michael,
The "Hatshepsut puzzle" is a scholarly mystery that reopens the case of one of the most exciting figures in Egyptian history: Hatshepsut, the first female pharaoh. The rediscovery of a nondescript flask in 2009 led to a thrilling hunt for the truth: what caused the death of this ruler? What hurdles did she have to overcome on her long road to power? In this volume, researchers of different specializations present their findings for the first time, giving us a surprisingly close and personal look at the life and death of the most unusual woman of antiquity.